JUNIOR HIGH SCHOOL PERCEPTION OF COOPERATIVE GROUP WORK - Puspita Nugraha WIbisono (Ma Chung Press, 2020)
Cooperative learning is not only about studying and sitting together, but it is more about structuring the group work. Structuring group work includes guidance of step by step to do the assignment. In the assessment process of group work, teachers tend to assess students individually, which is disassociated. To bridge the gap, representativeness assessment is introduced as a current insight. This study aimed to identify student’s perception toward cooperative group work strategies and representative assessment. In this research, data were collected through questionnaires from a population of students. The result of the study showed that the respondents showed high percentage of perception on both cooperative group work strategies and representative assessment.